Biomedical Applications of Metallosupramolecular Assemblies—Structural Aspects of the Anticancer Activity - Ahmedova, Anife (Frontiers in Chemistry, 2018)
The design and development of metallosupramolecular systems has resulted in construction of a myriad of fascinating structures with highly diverse properties and potential applications. Assessment of the biomedical applications of metallosupramolecular assemblies is an emerging field of research that stems from the recently demonstrated promising results on such systems. After the pioneering works of Therrien and coworkers on organometallic Ru-cages with promising anticancer properties, this topic has evolved to the more recent studies on bioactivity of supramolecular coordination complexes built from different metal ions and various multidentate ligands. Sufficient amount of data on the anticancer activity of metallosupramolecules has already been reported and allows outlining some general tendencies in the structural aspects of the biological activity. The main structural properties of the complexes that can be readily modified to enhance their activity are the size, the shape and charge of the formed complexes. Moreover, the intrinsic properties of the building components could predetermine some of the main characteristics of the overall supramolecular complex, such as its optical properties, chemical reactivity, solubility, etc., and could, thereby, define the areas of its biomedical applications. The unique structural property of most of the metallosupramolecular assemblies, however, is the presence of a discrete cavity that renders a whole range of additional applications resulting from specific host-guest interactions. The encapsulations of small bioactive or fluorescent molecules have been employed for delivery or recognition purposes in many examples. On the other hand, metallosupramolecules have been imbedded into target-specific polymeric nanoparticles that resulted in a successful combination of their therapeutic and diagnostic properties, making them promising for theranostic application in cancer treatment. The aim of this review paper is to mark out some key tendencies in the reported metallosupramolecular structures in relation with their biological activity and potential areas of biomedical application. In this way, a useful set of guidelines can be delineated to help synthetic chemists broaden the application areas of their supramolecular systems by few structural changes.